Electronic Medical Records as Evidence of Therapeutic Transactions - Putri, Prima Maharani; Saefudin, Yusuf (Jurnal Dinamika Hukum, 2021)
The results of the medical examination are proof of the doctor-patient relationship, which is documented in a record containing an explanation of the patient's health condition based on the results of the examination that has been carried out. Although the recording process is an obligation, there are several cases where medical records are not filled in correctly and some are not even filled in by officers. Therefore, this research is designed to find out the urgency of electronic medical records as evidence of therapeutic transactions. The problems studied in this article are: First, the juridical consequences of health workers and hospitals in making and keeping RM or RME confidential; Second, the position and strength of RM or RME as evidence according to the law of evidence. The results show that health workers or hospitals are obliged to make Medical Records or Electronic Medical Records correctly and responsibly. Regulation of the Minister of Health Number 749a/MENKES/Per/XII/1989 concerning Medical Records is the basis for the obligation to procure Medical Records, therefore it must be adhered to for every health service.Keywords: Medical Records, Electronic Medical Records, Evidence